An investigation of students' van Hiele levels of geometric thinking based on Chinese Mathematics curriculum - Zhang, Yu (Animo Repository, 2021)
A total of 97 students from two Grade 10 classes of a senior high school in Wuxi City, Jiangsu Province, China, participated in the study. The study aims to describe the geometric thinking level of Grade 10 students by using the van Hiele Geometry Test. The results show 87.7% of students reached the visualization level, 84.5% of students achieved the analysis level, 83.5% of students attained the abstraction level, 34% students reached the deduction level. The results imply that most Grade 10 students can reach level 2, but they are not good at reasoning skills and proof. In determining whether the Chinese Mathematics curriculum standards align with the van Hiele levels, data analysis shows that some students cannot analyze the characteristics and properties of figures and establish the relationship and theorems between different figures, and use intuition to solve problems. Most students cannot meet the requirements of the curriculum standards, especially in geometric reasoning. The study proposed to enhance the students' deduction reasoning ability by guiding students to understand the properties and theorems in geometry using vivid, exciting, and life-related geometric content to arouse students' interest in learning based on their intuition in mathematics. Allow students to learn the geometric content actively, cultivate their logical thinking ability, and improve their geometric thinking levels.